The influence of operational parameters on SO2 removal by limestone during fluidised bed coal combustion - Tarelho, Luís António da Cruz
Atmospheric Bubbling Fluidised Bed Combustion (ABFBC) of a bituminous coal and anthracite with particle size in the range 500–4000 Am was investigated in a pilot-plant facility, with and without limestone addition (particle size in range 710–1000 Am). The experiments were conducted at steady-state conditions using three excess air levels (10%, 25% and 50%) and bed temperatures in the 750–900 8C range. Combustion air was staged, with primary air accounting for 100%, 80% and 60% of total combustion air. Limestone addition is suitable for in-situ SO2 removal during ABFBC, with removal efficiencies in the range 25–85%. In general, the efficiency of SO2 removal by limestone decreases with an increase in air staging and a decrease in excess air. The increase in the bed temperature range 825–900 8C decreases the efficiency of SO2 removal by limestone, and in some situations a maximum can occur around 825 8C bed temperature. The reducing conditions at the first stage level, the secondary combustion, and the reductive decomposition of CaSO4 could be responsible for the low efficiency of SO2 removal by limestone during both high air staging and high bed temperatures.